Influence of PET reconstruction para meters on the TrueX algorithm - Knäusl, B.; Rausch, I. F.; Bergmann, H.; Dudczak, R.; Hirtl, A.; Georg, D. (Nuklearmedizin - NuclearMedicine, 2013)
With the increasing use of functional imaging in modern radiotherapy (RT) and the envisaged automated integration of PET into target definition, the need for reliable quantification of PET is growing. Reconstruction algorithms in new PET scanners employ pointspread-function (PSF) based resolution recovery, however, their impact on PET quantification still requires thorough investigation. Patients, material, methods: Measurements were performed on a Siemens PET/CT using an IEC phantom filled with varying activity. Data were reconstructed using the OSEM (Gauss filter) and the PSF TrueX (Gauss and Allpass filter) algorithm with all available products of iterations (i) and subsets (ss). The recovery coeffcient (RC) and threshold defining the real sphere volume were determined for all settings and compared to the clinical standard (4i21ss). PET acquisitions of eight lung patients were reconstructed using all algorithms with 4i21ss. Volume size and tracer uptake were determined with different segmentation methods. Results: The threshold for the TrueX was lower (up to 40%) than for the OSEM. The RC for the different algorithms and filters varied. TrueX was more sensitive to permutations of i and ss and only the RC of the OSEM stabilised with increasing number. For patient scans the difference of the volume and activity between TrueX and OSEM could be reduced by applying an adapted threshold and activity correction. Conclusion: The TrueX algorithm results in excellent diagnostic image quality, however, guidelines for native algorithms have to be extended for PSF based reconstruction methods. For appropriate tumour delineation, for the TrueX a lower threshold than the 42% recommended for the OSEM is necessary. These filter dependent thresholds have to be verified for different scanners prior to using them in multicenter trials.
Keywords: Reconstruction algorithms; TrueX; recovery coefficient; phantom measurements; segmentation